Advanced Exergy-Based Analysis of an Organic Rankine Cycle (ORC) for Waste Heat Recovery - Zineb Fergani; Tatiana Morosuk (Entropy, 2023)
In this study, advanced exergy and exergoeconomic analysis are applied to an Organic Rankine Cycle (ORC) for waste heat recovery to identify the potential for thermodynamic and economic improvement of the system (splitting the decision variables into avoidable/unavoidable parts) and the interdependencies between the components (endogenous and exogenous parts). For the first time, the advanced analysis has been applied under different conditions: constant heat rate supplied to the ORC or constant power generated by the ORC. The system simulation was performed in Matlab. The results show that the interactions among components of the ORC system are not strong; therefore, the approach of component-by-component optimization can be applied. The evaporator and condenser are important components to be improved from both thermodynamic and cost perspectives. The advanced exergoeconomic (graphical) optimization of these components indicates that the minimum temperature difference in the evaporator should be increased while the minimum temperature difference in the condenser should be decreased. The optimization results show that the exergetic efficiency of the ORC system can be improved from 27.1% to 27.7%, while the cost of generated electricity decreased from 18.14 USD/GJ to 18.09 USD/GJ.